Kiusanhenki: Satu - Hoffmann, E. T. A. (Ernst Theodor Amadeus), 1776-1822; Tuomikoski, Aino, 1889-1958 (Salt Lake City, UT : Project Gutenberg, 2016)
"Kiusanhenki: Satu" by E. T. A. Hoffmann is a work of fiction written in the early 19th century. The story appears to explore themes of hardship, societal perceptions, and the intersection of the mundane with the fantastical, focusing on characters such as a struggling peasant woman and her grotesquely deformed son, referred to as Sakeus. As the narrative unfolds, it promises a blend of social commentary and magical realism, amid the backdrop of folk tales and the supernatural. The opening of the story introduces a peasant woman who is beset by poverty and despair, lamenting her situation as she prepares to return home with a heavy burden of firewood. She expresses her frustration with the hardships she faces alongside her husband, particularly highlighting their son, the "little changeling," who has become the village's source of shame due to his deformities. As her sorrow overwhelms her, the story introduces a compassionate character, the noble maid Ruusunihana, who intervenes to provide comfort. This sets the stage for a narrative rich with emotional depth, character conflict, and the potential for transformation, hinting at the intertwining fates of all characters involved. (This is an automatically generated summary.)
Release date is 2016-10-05
Produced by Timo Ervasti and Tapio Riikonen
Keywords: Fantasy fiction; Fairy tales -- Germany -- Translations into Finnish